Moral Thought of Early Childhood in Perspective Lawrence Kohlberg - Afifah Fatihakun Ni'mah Wahidah; Maemonah Maemonah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
This paper seeks to explain the moral development of early childhood in the view of Lawrence Kohlberg. Research on Kohrlberg's development so far has been more targeted at the development of elementary age students to adults. This paper tries to analyze moral development at an early age, or age 4-6 years. Early Childhood according to Kohrlberg experienced a phase of moral development in the first stage (pre-conventional phase). In this period the child's moral development is influenced by the behavior of adults around the child (role model). The moral development of children does not occur suddenly but is attempted and intentional, in other words to achieve moral development in early childhood it is necessary to have moral education for early childhood. The interesting thing is that this moral development is always biased with a sense of injustice. Lawrence Kohlberg suggested that in conducting moral education should always be done with a sense of justice. Because justice is a major recognition of the same level and position, and become the most basic and general measuring tool. This discussion uses the method of library research. The results of this study indicate that educators (teachers) especially in early childhood in understanding the moral development of children, in addition to going through stages of moral development must also pay attention to justice in applying the stages of moral development.Keywords: Thought Lawrence Kohlberg, Early Childhood, Education Abstrak Tulisan ini berusaha menjelaskan tentang perkembangan moral anak usia dini dalam pandangan Lawrence Kohlberg.Penelitian tentang perkembangan Kohrlberg selama ini lebih banyak menyasar pada perkembangan peserta didik usia dasar sampai dewasa.Tulisan ini mencoba menganalisis perkembangan moral pada usia dini, atau usia 4-6 tahun. Anak Usia Dini menurut Kohrlberg mengalami fase perkembangan moral pada tahap yang pertama (fase pra konvensional). Pada masa ini perkembangan moral anak dipengaruhi oleh perilaku orang dewasa disekitar anak (suri tauladan). Perkembangan moral anak tidak terjadi dengan tiba-tiba tapi diusahakan dan disengaja, dengan kata lain untuk mencapai perkembangan moral anak usia dini maka perlu adanya pendidikan moral untuk anak usia dini. Hal yang menarik adalah bahwa perkembangan moral ini selalu biasdengan rasa ketidakadilan. Lawrence Kohlberg menyarankan dalam melakukan pendidikan moral hendaknya selalu dilakukan dengan rasa keadilan.Karena keadilan adalah suatu pengakuan utama terhadap tingkat dan kedudukan yang sama, dan menjadi alat ukur yang paling dasar dan umum.Pembahasan ini memakai metode penelitian kepustakaan. Hasil dari penelitian ini menunjukkan bahwa pendidik (guru) terutama pada anak usia dini dalam memahmi perkembangan moral anak, disamping melalui tahapan-tahapan perkembangan moral juga harus memperhatikan keadilan dalam menerapkan tahapan perkembangan moral.Kata kunci: Pemikiran Lawrence Kohlberg, Anak Usia Dini, Pendidikan